2014
DOI: 10.1017/s0033291714001202
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic growth among veterans in the USA: results from the National Health and Resilience in Veterans Study

Abstract: PTG is prevalent among US veterans, particularly among those who screen positive for PTSD. These results suggest that there may be a 'positive legacy' of trauma that has functional significance for veterans. They further suggest that interventions geared toward helping trauma-exposed US veterans process their re-experiencing symptoms, and to develop greater social connections, sense of purpose and intrinsic religiosity may help promote PTG in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
162
2
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(183 citation statements)
references
References 52 publications
13
162
2
6
Order By: Relevance
“…They suggest that individuals tend to be intrinsically motivated toward rebuilding their schemas or assumptive worlds toward growth and actualization after facing traumatic events. Furthermore, Tsai et al (2015a) found a significant relationship between PTSD and PTG, but this relationship was curvilinear. Specifically, traumaexposed veterans reporting moderate PTSD levels had the greatest PTG levels (Tsai et al, 2015a).…”
Section: Relationship Between Ptsd and Ptgmentioning
confidence: 92%
See 2 more Smart Citations
“…They suggest that individuals tend to be intrinsically motivated toward rebuilding their schemas or assumptive worlds toward growth and actualization after facing traumatic events. Furthermore, Tsai et al (2015a) found a significant relationship between PTSD and PTG, but this relationship was curvilinear. Specifically, traumaexposed veterans reporting moderate PTSD levels had the greatest PTG levels (Tsai et al, 2015a).…”
Section: Relationship Between Ptsd and Ptgmentioning
confidence: 92%
“…Furthermore, Tsai et al (2015a) found a significant relationship between PTSD and PTG, but this relationship was curvilinear. Specifically, traumaexposed veterans reporting moderate PTSD levels had the greatest PTG levels (Tsai et al, 2015a). These studies did not examine possible relationships among the factors of both PTSD and PTG, however.…”
Section: Relationship Between Ptsd and Ptgmentioning
confidence: 92%
See 1 more Smart Citation
“…Data were analyzed from 1484 veterans who participated in the second baseline assessment (conducted SeptembereOctober, 2013), which included administration of the DSM-5 version of the PTSD Checklist. Several previous studies have been conducted on data from the first baseline assessment of the NHRVS, which included a different cohort of veterans and did not use the most recent version of the PTSD Checklist (Pietrzak and Cook, 2013;Tsai et al, 2015a).…”
Section: Samplementioning
confidence: 99%
“…Shiri et al (2008) reported that immediacy and proximity to violence were associated with increased posttraumatic growth. Tsai et al (2015) found that the traumatic event most strongly associated with posttraumatic growth was life-threatening illness or injury. They also found that several psychosocial factors, namely, social connectedness, intrinsic religiosity, and purpose in life, were independently related to posttraumatic growth (Tsai et al, 2015).…”
mentioning
confidence: 99%